A Study on Maker Teaching Activity Design in Senior High School General Technology Course for Creativity Cultivation - Wang, Hongjiang; Ye, YuanFen; Liao, Xiaoling; Li, Zuokun; Liang, Yingli (Frontiers in Psychology, 2022)
General Technology Course (GTC) in senior high school focuses on skill training and the connection and comprehensive application of interdisciplinary knowledge, and it is a compulsory course for cultivating students' creative potential. However, GTC in domestic senior high school has low teaching efficiency and fails to cultivate students' creativity well. Fortunately, after years of theoretical and practical research in China, the Maker Education (ME), which focuses on cultivating students' innovative ability, has produced well-recognized applied research results. For this reason, this paper integrates the theories of ME into GTC. Combined the characteristics of ME and GTC, and followed the process of creation and the law of the expression of personality traits, we build a model of GTC based on ME to improve students' creativity effectively. In order to improve and optimize the designed teaching model, this study carried out three rounds of Action Research, designed the practical activities of GTC in senior high school, and revised the teaching model through action, observation and reflection continuously. Finally, this paper designed an experimental group and a control group. The experimental group adopts the recommended General Technology teaching model, and the control group adopts the traditional teaching model. Students were asked tested to take pre-test and post-test, and SPSS was used for analysis of ANCOVA and T-test. After analysis, the following experimental results were obtained: (1) the teaching model proposed in this paper can improve students' creativity significantly and effectively; (2) the adventurous, curiosity, imagination, challenge of students also have significant positive improvement.